EFFECTS OF BIOFERTILIZER CONTAINING MICROBIAL OF N-FIXER, P SOLUBILIZER AND PLANT GROWTH FACTOR PRODUCER ON CABBAGE (BRASSICA OLERACEAE VAR. CAPITATA) GROWTH AND SOIL ENZYMATIC ACTIVITIES: A GREENHOUSE TRIAL - Sarjiya Antonius; Dwi Agustiyani (The East Java Biological Society, 2011)
Biofertilizer has been identified as an alternative to chemical fertilizer to increase soil fertility and crop production in sustainable farming. The objective of this greenhouse study was to evaluate the effects of four different concentrations of biofertilizers containing Pseudomonas sp., Bacillus sp. and Streptomyces sp. on soil properties and to evaluate the growth of Brassica oleraceae var. capitata. The application treatments included control (no fertilizer) and four concentration of diluted biofertilizer per pot (20 ml, 40 ml, 60 ml and 80 ml). The application of biofertilizer containing benefi cial bacteria signifi cantly increased the growth of B. oleraceae. The use of biofertilizer resulted higher biomass weight and length as well as root length. This greenhouse study also indicated that different amount of biofertilizer application had almost similar effects. Microbial inoculum not only increased plant harvest, but also improved soil properties, such as number of microorganisms, respiration and urease activities.